The Theoretical Framework of Cashless Payment Systems in Indonesia: Analyzing Condition in Different Era’s - Septiningrum, Lutfia; Agustanta, Nainta; Ahdiyana, Marita; Wahyu Widianto, Hardian; Pambudi, Argo (Natapraja, 2024)
This study explores the influence of government policies and initiatives across different presidential eras in Indonesia on the development and adoption of cashless payment systems, with a particular focus on the implementation of QRIS (Quick Response Code Indonesian Standard). It examines how these policies, including digital literacy programs and regulatory frameworks, have shaped public perceptions and acceptance of digital payment solutions. The research also investigates the social, economic, and technological factors that contribute to the increasing acceptance of cashless payments and their impact on financial inclusion and economic behaviors. The findings indicate that government efforts, such as promoting QRIS and enhancing financial regulations, have significantly accelerated the transition from cash-based to digital transactions, especially during the COVID-19 pandemic. However, challenges remain, particularly concerning low digital financial literacy (around 25%) and security threats such as fraud and fake QR codes. Overall, the rapid growth in QRIS users—reaching over 48 million consumers and 32 million merchants as of 2024—demonstrates a positive trajectory toward Indonesia’s goal of a more inclusive, efficient, and secure cashless economy. The study underscores the importance of continued policy support, public education, and technological innovations to overcome existing barriers and sustain the momentum of Indonesia’s digital payment transformation